2014
DOI: 10.1371/journal.pone.0107236
|View full text |Cite
|
Sign up to set email alerts
|

Family with Sequence Similarity 5, Member C (FAM5C) Increases Leukocyte Adhesion Molecules in Vascular Endothelial Cells: Implication in Vascular Inflammation

Abstract: Identification of the regulators of vascular inflammation is important if we are to understand the molecular mechanisms leading to atherosclerosis and consequent ischemic heart disease, including acute myocardial infarction. Gene polymorphisms in family with sequence similarity 5, member C (FAM5C) are associated with an increased risk of acute myocardial infarction, but little is known about the function of this gene product in blood vessels. Here, we report that the regulation of the expression and function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Translocation of p65 of NFκB from cytoplasm to nucleus is recognized as a prerequisite for the transcription 25 . VCAM-1 and ACAT-1 expressions at sites of atherosclerotic lesion formation are majorly controlled by NFκB system in early atherosclerotic lesions 26 . We found that salusin-β induced p65-NFκB nuclear translocation and recruitment of p65 to promoters of ACAT-1 and VCAM-1 in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Translocation of p65 of NFκB from cytoplasm to nucleus is recognized as a prerequisite for the transcription 25 . VCAM-1 and ACAT-1 expressions at sites of atherosclerotic lesion formation are majorly controlled by NFκB system in early atherosclerotic lesions 26 . We found that salusin-β induced p65-NFκB nuclear translocation and recruitment of p65 to promoters of ACAT-1 and VCAM-1 in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…62 BRINP3 expression is also implicated in the modulation of reactive oxygen species production and NF-kB activity with downstream effects on leukocyte adhesion and inflammation in humans. 64 Although the peak lies a considerable distance from BRINP3, it is relatively narrow and is supported by a large number of SNPs ( Figure 3A), possibly including cis-regulatory elements.…”
Section: Top Candidate Genesmentioning
confidence: 93%
“…However, the expression level of BRINP3 was low in iPSCs, therefore, we cannot exclude the possibility that this result was an artifact. Nevertheless, the Chr1-eGSH locus may not be a suitable locus for therapeutic gene integration, as BRINP3 could be associated with pituitary gonadotropinomas [43] and inflammation [44], Notably, CTCF ChIA-PET analysis predicted this distant interaction, which has not been previously reported [40]. Although we used a public ChIA-PET dataset which was not generated from hiPSCs, our results suggested that bioinformatics approaches could be powerful tools for exploring the ideal human GSH and predicting the effect of genome editing.…”
Section: Discussionmentioning
confidence: 99%